Pelatihan Komputer dan Internet untuk Perangkat Desa Pancoran Kecamatan Bondowoso Kabupaten Bondowoso - Daryanto Daryanto; Zainul Arifin (Indonesian Journal Publisher, 2022)
Administratively, Pancoran Village is led by a Village Head who leads 12 section heads, consisting of 1 secretary, 7 heads of affairs, and 4 hamlet heads. Each of these section heads is assisted by other village officials to carry out their duties in community service. In carrying out its obligations, especially those related to village administration and licensing, ideally village officials have competence in the computer sector. However, from the village apparatus report, the village apparatus who mastered basic computer material, in this case was Microsoft Office (Word, Power Point, and Excel), only one person was not optimal.